Effect of Portulaca oleracea and Lolium perenne in native chicken meat - Ángeles-Coronado, Imelda Adriana; Jerez-Salas, Martha Patricia; Pérez-León, María Isabel; Villegas-Aparicio, Yuri (Revista Mexicana de Ciencias Agrícolas, 2018)
The effect of purslane (Portulaca oleracea L) and ryegrass (Lolium perenne) on yield and chemical characteristics of native chicken meat was evaluated. The research was conducted at the Technological Institute of Oaxaca Valley during 2011 and 2012, determining the live weight, losses due to non-meat components, major cuts weight, protein content, fat, minerals and moisture for breast , legs and thigh from native chicken of 64 weeks old fed with alternative diet (43% corn, 39% peanut, 13.5% alfalfa, 02.5% calcium carbonate, 0.5% calcium phosphate, 0.5% minerals, 0.5% vitamins and 0.5% salt) plus grazing in Portulaca oleracea L., (T1), alternative diet plus grazing in Lolium perenne (T2) and commercial food for birds (control T0). The highest live weight and heavier carcass was obtained from animals fed with T1, in the losses for non-meat components T2 had the lowest yield. The percentage weight for cuts between T1 and T2 had no effect (p> 0.05). In concentration of protein, fat, minerals and moisture T1 had better yield revealing the higher concentrations of protein, fat, minerals and lesser concentration in water content.
Keywords: Portulaca oleracea L.; Lolium perenne; quality; yield